2019
DOI: 10.1111/jgh.14757
|View full text |Cite
|
Sign up to set email alerts
|

Simethicone use during gastrointestinal endoscopy: Position statement of the Gastroenterological Society of Australia

Abstract: Concern has been raised regarding the use of simethicone, a de-foaming agent, during endoscopic procedures. Following reports of simethicone residue in endoscope channels despite high level disinfection, an endoscope manufacturer recommended that it not be used due to concerns of biofilm formation and a possible increased risk of microorganism transmission. However, a detailed mucosal assessment is essential in performing high-standard endoscopic procedures. This is impaired by bubbles within the gastrointesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 18 publications
1
31
0
1
Order By: Relevance
“…Simethicone is also called poly-dimethylsiloxane, which has been introduced to remove the foam and water. Recent studies have reported that the administration of simethicone before endoscopic examination could shorten the procedure time and improve the diagnostic rate of the gastric mucosal lesions [6][7]. Although simethicone has been routinely administrated before the esophagogastroduodenoscopy, the optimal strategy of administrating simethicone has not been clearly investigated, especially the time interval from simethicone administration to the endoscopic procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Simethicone is also called poly-dimethylsiloxane, which has been introduced to remove the foam and water. Recent studies have reported that the administration of simethicone before endoscopic examination could shorten the procedure time and improve the diagnostic rate of the gastric mucosal lesions [6][7]. Although simethicone has been routinely administrated before the esophagogastroduodenoscopy, the optimal strategy of administrating simethicone has not been clearly investigated, especially the time interval from simethicone administration to the endoscopic procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Simethicone is an effective antifoaming agent during endoscopic procedures. The Gastroenterological Society of Australia consensus panel found that the current evidence supported the use of simethicone for improving visibility and likely facilitates adenoma detection at colonoscopy [33]. In addition, a recently study reported that a 10% increase in the detection rate of colorectal polyp when simethicone is added to the water pump during colonoscopy [34].…”
Section: Discussionmentioning
confidence: 97%
“…The addition of 2-3 mL of 120 mg/mL simethicone to lavage uid was recommend [33]. In the subgroup analysis, we compared the effect of the low dose simethicone (< 400 mg) versus that of high dose simethicone (≄ 400 mg) for ADR and PDR.…”
Section: Discussionmentioning
confidence: 99%
“…21 However, the technique of using simethicone as an orally taken solution is safe and does not damage the endoscope(s). 22 We thus present a simple technique of improving the mucosal visibility by using a pre-endoscopic drink of NAC + simethicone. To the best of our knowledge, this is the first Indian study evaluating the outcomes of a simple pre-endoscopy preparation.…”
Section: Discussionmentioning
confidence: 99%